Estudo fitoquímico e biológico da Tacinga palmadora (Britton & Rose) N.P. Taylor & Stuppy (cactaceae) - Peixoto, Laisla Rangel (2018)
The palmadora, belonging to the family Cactaceae, is a plant popularly known as Palmatoria, Palma or Quipá. The T. palmadora is widely distributed in areas of the Caatinga of the Northeast region of Brazil, the tea of its root being popularly used in the treatment of problems in the urethra. The present study aimed to isolate chemical compounds from the extracts and phases obtained, perform the physicochemical characterization of the plant drug, as well as to investigate biological activities of the roots of the species T. palmadora. After harvesting, the roots were dried and crushed to obtain the vegetable drug. The physicochemical characterization of the plant drug was used to determine the granulometry, density, ash content, moisture content, pH, microstructure (Scanning Electron Microscopy (SEM) and Dispersive Energy (EDS)), Infrared Region Spectroscopy with Fourier Transform (FTIR), Thermogravimetric Analysis (TG) and Differential Thermal Analysis (DTA). The crude ethanol extract (EEB), the nebulized hydroalcoholic extract (EHAN), and the hexane and hexane phases (Hex), Dichloromethane (CH 2 Cl 2), Ethyl Acetate (AcOEt) and Ethanolol (EtOH) were obtained from the root of T.palmadora. In addition, qualitative and quantitative phytochemical screening was performed. Isolation and identification of the chemical compounds were performed by chromatographic and spectroscopic methods, respectively. The toxicological activity against Artemia salina, Determination of Minimal Inhibitory Concentration (MIC) for bacteria and fungi, hemolytic tests and antioxidant activity, using the DPPH (2,2-diphenyl-1-picryl- hydrazyl), Total Antioxidant Activity (AAT) and the Ferric Thiocyanate method. The powder was classified as semi-thin, easy flow, low moisture content and average pH value of 5.58. The data obtained by qualitative phytochemical screening showed positive results for alkaloids and steroids / triterpenoids. TG analysis of the plant drug showed the occurrence of three stages of mass loss. The DTA analysis showed two endothermic and one exothermic events. The phytochemical study of T. palmadora roots resulted in the isolation of 4 compounds, an ester derived from caffeic acid, 5- hydroxy-4 ', 7-dimethoxyflavone, vanillic acid and ethyl palmitate. It was observed that the values of the Lethal Concentration (LC50) of the extracts showed little significant activity (LC50> 1000 μg.mL-1). The extracts AcOEt, EtOH and Hex showed antifungal activity against C. albicans, C. krusei and C. tropicalis. The EtOH extract showed the highest hemolytic activity. The antioxidant activity, as well as the capacity of sequestration of DPPH, the extract AcOEt obtained the best result, where in the concentration of 500 μg.mL-1 obtained an average of 76.44% and for the AAT, the extract AcOEt showed a better result, since the results were similar to the Quercetin standard. T.palmadora has been shown to be a promising species, due to the variety of isolated chemical compounds and important biological activities. Further chemical, pharmacological and toxicological studies should be done to promote knowledge about this plant.